Mathematics of interest rates and finance - Guthrie, Gary C.; Lemon, Larry D. (Pearson Education, 2011)
This book presents the basic core of information needed to understand the impact of interest rates on the world of investments, real estate, corporate planning, insurance, and securities transactions.